2021
DOI: 10.32734/idjpcr.v4i1.5382
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Acne Activity From Biocellulose Mask Formula Containing (Aloe Vera (L.) Burm.F) Essence Combined With Vitamin E

Abstract: Abstract. Biocellulose mask sheet is a new found pharmaceutical cosmetic design that widely commercial. Mostly due to it’s biodegradable properties, provide an eco-friendly waste. Combination of Aloe vera essence (AE) and Vit E to provide and determine it’s respective anti-acne properties in biocellulose mask form. Formulation of biocellulose mask with the help of Acetobacter xylinum bacteria varied with different formulae: F1 (Vitamin E 1%), F2 (E 2.5 %), F3 (AE 5%), F4 (AE 2.5%+Vit E 1%) and F5 (AE 5%+Vit E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…The pH of the preparation greatly affects whether the formulation that is formulated is able to irritate the user or not. The results of the formulations showed that the pH of each formula was in the range of 4-5 [34]. Based on SNI No.…”
Section: Homogenitymentioning
confidence: 99%
“…The pH of the preparation greatly affects whether the formulation that is formulated is able to irritate the user or not. The results of the formulations showed that the pH of each formula was in the range of 4-5 [34]. Based on SNI No.…”
Section: Homogenitymentioning
confidence: 99%
“…Incubated at 36 oC for 24 hours, the treatment was repeated three times. Then the zone of inhibition was measured with a caliper (mm) [14], [15].…”
Section: Determination Of Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…One sample of revitalized bacteria was suspended in a test tube containing 10 mL of MHB medium, vortexed, and turbidity was adjusted using 0.5 McFarland standards 7,13 .…”
Section: Preparation Of Bacterial Suspensionmentioning
confidence: 99%